BOOSTING IMMUNITY: NATURAL AND SYNTHETIC APPROACHES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This thesis presents a critical analysis of the diverse strategies aimed at modulating and enhancing immune function, examining the evidence base, mechanisms of action, and practical applications of both natural and synthetic approaches. The central objective is to distinguish evidence-based interventions from popular myths and provide a scientifically grounded framework for immune support. The thesis evaluates the strength of scientific evidence for common practices, addresses the commercialization of the "immune-boosting" industry, and emphasizes that the most effective strategy is a holistic lifestyle approach that supports the complex, interconnected systems governing immune function. It concludes that while targeted synthetic interventions are irreplaceable for specific deficiencies or diseases, foundational natural lifestyle practices provide the essential substrate for optimal, balanced immune competence in the general population.